13+2r=3r+7

Simple and best practice solution for 13+2r=3r+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+2r=3r+7 equation:


Simplifying
13 + 2r = 3r + 7

Reorder the terms:
13 + 2r = 7 + 3r

Solving
13 + 2r = 7 + 3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3r' to each side of the equation.
13 + 2r + -3r = 7 + 3r + -3r

Combine like terms: 2r + -3r = -1r
13 + -1r = 7 + 3r + -3r

Combine like terms: 3r + -3r = 0
13 + -1r = 7 + 0
13 + -1r = 7

Add '-13' to each side of the equation.
13 + -13 + -1r = 7 + -13

Combine like terms: 13 + -13 = 0
0 + -1r = 7 + -13
-1r = 7 + -13

Combine like terms: 7 + -13 = -6
-1r = -6

Divide each side by '-1'.
r = 6

Simplifying
r = 6

See similar equations:

| 3(5-x)=9(15x-5) | | x/8=54 | | 3.75+3y=6 | | f(x)=8-7(4x+2) | | 2x+9=1x+1 | | 6x+3(2x+2)=102 | | 31=x+2x+(3x+1) | | 2x^2-5x-12.5=0 | | 2x^2-5x-12.51=0 | | 5x+7y/3(x+y) | | -3x-4=-6-5x | | 3x+5(25-x)=89 | | 7x+12y=34 | | 2(x+2)=3(x+6) | | 7x+12y=86 | | 3x+5(25-5)=89 | | 4(X+1)-2=6(5-X)+3 | | -3-2(x+4)=25 | | ln(2x+6)=-10 | | f(x)=4-x^2+5x^2 | | 2/3x=-3/5 | | fx=4-x^2+5x^2 | | 3x+5(5x-8)=156 | | Y+a+b+c/6 | | -3+6x+x^2=0 | | 44=2(3x+4) | | 3(3x+9)=9x+27 | | 2x^2+3y-5x=-3 | | 5x+2=23-2x | | 4y(5y-2)=122 | | 4-(5X+7)=6-(X-3) | | 4yx(5y-2)=122 |

Equations solver categories